2014
DOI: 10.2139/ssrn.2487069
|View full text |Cite
|
Sign up to set email alerts
|

Applying 'Benford's Law' to the Crosswise Model: Findings from an Online Survey on Tax Evasion

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Recent studies have reported very good performance with the crosswise model in applications ranging from cheating by undergraduates to tax evasion (Jann, Jerke, and Krumpal ; Körndorfer, Krumpal, and Schmukle ; Kundt ).…”
mentioning
confidence: 99%
“…Recent studies have reported very good performance with the crosswise model in applications ranging from cheating by undergraduates to tax evasion (Jann, Jerke, and Krumpal ; Körndorfer, Krumpal, and Schmukle ; Kundt ).…”
mentioning
confidence: 99%
“…In addition, seven studies (Shamsipour et al, 2014;Khosravi et al, 2015;Nasirian et al, 2018;Banayejeddi et al, 2019;Hopp and Speil, 2019;Safiri et al, 2019;Schnapp, 2019) used a combination of birthday and non-birthday innocuous item pairs. Phone numbers were used in seven studies (Shamsipour et al, 2014;Khosravi et al, 2015;Vakilian et al, 2016Vakilian et al, , 2019Kundt et al, 2017;Banayejeddi et al, 2019;Safiri et al, 2019), house numbers in seven studies (Kundt, 2014;Shamsipour et al, 2014;Khosravi et al, 2015;Lehrer et al, 2019;Safiri et al, 2019;Schnapp, 2019;Vakilian et al, 2019), ATM card pin code in three studies (Shamsipour et al, 2014;Khosravi et al, 2015;Safiri et al, 2019), and ID card number in two studies (Khosravi et al, 2015;Safiri et al, 2019). The remaining studies relied on random numbers or letters of the alphabet (Banayejeddi et al, 2019), performance of academic tasks (Jerke et al, 2021), date of a significant personal event (Hopp and Speil, 2019), family size of four (Nasirian et al, 2018), owning a vehicle (Nasirian et al, 2018), friend or family member with a common name (Vakilian et al, 2014(Vakilian et al, , 2019, picking a card (Mirzazadeh et al, 2018), and random probability assignment (Atsusaka and Stevenson, 2020).…”
Section: Innocuous/unrelated Itemsmentioning
confidence: 99%
“…Of these, 49 pairs used specific birthday months with P ranging between 0.08 (1/12 months) and 0.25 (3/12 months). In five cases (Eslami et al, 2013;Nakhaee et al, 2013;Khosravi et al, 2015;Nasirian et al, 2018;Safiri et al, 2019), season (e.g., spring) was used which is open for interpretation Substance use and misuse Nakhaee et al, 2013;Shamsipour et al, 2014;Höglinger et al, 2016;Mirzazadeh et al, 2018;Banayejeddi et al, 2019;Safiri et al, 2019;Özgül, 2020;Canan et al, 2021Shamsipour et al, 2014Mirzazadeh et al, 2018;Safiri et al, 2019 Academic misconduct Coutts et al, 2011;Jann et al, 2012;Höglinger et al, 2016;Hopp and Speil, 2019;Jerke et al, 2021Coutts et al, 2011Jann et al, 2012;Jerke et al, 2021 Corruption, tax evasion, and theft Korndörfer et al, 2014;Kundt, 2014;Gingerich et al, 2015;Höglinger and Jann, 2018;Hopp and Speil, 2019;Oliveros and Gingerich, 2020 Health and STDs Mirzazadeh et al, 2018;Nasirian et al, 2018 Sexual behavior and infidelity Mirzazadeh et al, 2018;Klimas et al, 2019;Lacker et al, 2020 Substance use and misuse Khosravi et al, 2015;Kazemzadeh et al, 2016;Heck et al, 2018;…”
Section: Model Designmentioning
confidence: 99%
See 2 more Smart Citations